Fluororubber superhydrophobic coating: preparation, characterisation, and EMI shielding performance. (3rd October 2021) - Zhou, Wen Yan; Phule, Ajit Dattatray; Ma, Le Yuan; Shan, Ti Kun; Guo, Jianzhang; Zhang, Zhen Xiu
ABSTRACT: Herein, we report the preparation and characterisation of fluororubber coated superhydrophobic Poly (ethylene tetrapthalate) (PET) fabric and polyurethane (PU) sponge. The coating surface structure over PET fabric is more stable and hydrophobic (water contact angle (CA) ≥ 153°) with mass ratio 5:1 of fluororubber/carbon nanotubes (CNTs). Fluororubber/CNT coated PET fabric has good wear resistance and hydrophobicity with repeated friction. PU sponge coated with the ratio 8:4 of fluororubber/carbon black (CB) is the best ratio showing water CA ≥ 157°. Fluororubber/CB coated PU sponge has good oil-water separation and repeated oil absorption ability. Its absorption ability to various solvents and oils can reach 20–50 times its own weight. The EMI SE of fluororubber coating in 8.2–12.4 MHz range has improved with the increased CNTs content. The highestEMI SE valuee, i.e. 52.30 db achieved at 2.0 wt% CNT content. Developed fluororubber superhydrophobic coating material has good potential in the EMI shielding application.